Anti-tumour and immunomodulatory activities of a polysaccharide fraction from Solanum nigrum L. Nigrum towards breast cancer / Faizan Naeem Razali - Faizan Naeem , Razali (2017)
Breast cancer is the most frequently diagnosed cancer worldwide. In the year of 2012, approximately 1.67 million new incidences were reported, with a mortality rate of 15.4%. Approximately 5,410 of Malaysian women were affected, with the mortality rate of 11.9% reported in the same year. Conventional therapies for cancer indeed improve mortality and cure rate in patients. However, the side effects due to toxicity of the therapeutic agents are unavoidable and negatively affecting patient’s quality of live. Solanum nigrum is an herbal plant that has been extensively studied because of folklore belief that this plant has various health benefits, including curing cancer. Currently, immunotherapy is gaining much interest among pharmacologist as an approach in cancer treatment. The aim of this study was to evaluate the ability of S. nigrum extract to inhibit breast cancer progression through immunomodulation. In the in vitro study, the immunomodulating activity of polysaccharide extract from S. nigrum was analysed by looking at its effects on RAW 264.7 murine macrophage cells. Crude polysaccharide extracted from the stem of S. nigrum was partially purified through ion-exchange chromatography, yielding five polysaccharide fractions. The fractions were then evaluated for cytotoxicity and nitric oxide production. The ability of the polysaccharide extracts to activate macrophages and to induce phagocytosis and cytokine production were also measured. Though not cytotoxic (IC50 > 100 mg/kg), all polysaccharide fractions were able to induce nitric oxide production in RAW 264.7 cells. Of the five fractions tested, SN-ppF3 had the lowest cytotoxicity and induced the highest amount of nitric oxide, which tally with the increase in inducible nitric oxide synthase expression detected in the cell lysate. This fraction also significantly induced phagocytic activity and stimulated the production of tumour necrosis factor- and interleukin-6. Based on the cytokines produced, it could be concluded that classically activated macrophages could be induced by SN-ppF3. The in vitro results confirmed that SN-ppF3 possessed the immunomodulatory effect, and in vivo evaluation was carried out to further analyse the possible mechanism on how SN-ppF3 could inhibit tumour progression in 4T1 tumour-bearing BALB/c mice. The sample dose of 500 mg/kg/bw was shown to have non-toxic effect to the healthy mice as 100% of the mice were alive after 14 days of treatment (n=5). Tumour volume and weight were significantly (p<0.05) inhibited by 65% and 40% respectively after oral administration of 500 mg/kg of SN-ppF3 for 10 days (n=6). To further analyse the ability of SN-ppF3 in suppressing tumour progression, the production of cytokines in the serum were evaluated. The level of tumour necrosis factor-, interferon-γ and interleukin-4 were significantly (p<0.05) elevated by 12%, 22% and 12% respectively, while the level of interleukin-6 was decreased by 52%. Histological observations showed that treatment with SN-ppF3 resulted in disruption of cell morphology due to apoptosis and enhanced the infiltration capability of natural killer cells and cytotoxic T cells directly into the solid tumour. These results suggested that the treatment of tumour-bearing mice with SN-ppF3 was able to suppress tumour progression by improving host immune responses thus potentially develop as novel anti-tumour agent.